Social networking through email: studying email usage patterns of persons with aphasia. Issue 2 (3rd March 2016) - Al Mahmud, Abdullah; Martens, Jean-Bernard
Abstract : Background : A social networking program has been developed by the Aphasia Union Netherlands (AVN) to enhance communication between older persons with aphasia (PWA) mutually and with their therapists. The medium of communication is email. Aims : The aim of the paper is to understand the email usage patterns of PWA. Methods & Procedures : We evaluated the email program in two ways, i.e., by analysing the AVN email server logs and by collecting subjective responses through questionnaires. The log data that we analysed were over 4 years (2007–2010). Outcomes & Results : Our results indicate that both PWA and therapists find the email program useful, despite the fact that they expressed several criticisms about its usability. We have found from the log results that there were three types of users utilising the email program. Group 1 registered to use the program but never used it; Group 2 started using the program after registration and after some time stopped using it. And finally Group 3 is still active in email exchange but the frequency is rather low. In total there were 326 users (146 PWA and 180 persons who did not have aphasia) who generated email messages; 119 PWA sent email messages. A small number of the PWA (6 out of 119) sent messages without receiving them, while the majority (113 out of 146) of them sent and received messages. Of the 9996 email messages sent (from July 2007 to December 31, 2010), 80.1% (8010) email messages were sent by PWA and 19.9% (1986) email messages were sent by persons who did not have aphasia. It is a good sign that the majority of the email messages were sent by PWA, as they are the primary users of the social network site. It has also been revealed from the data analysis that overall only 10% of the messages contain image attachments. Conclusions : Even though several design aspects need to be considered to improve the program, the current design is a promising first step. The lessons learned from the evaluation of the AVN email program can be helpful for designing social networking sites for other people with disabilities.